2013
DOI: 10.1002/chem.201203069
|View full text |Cite
|
Sign up to set email alerts
|

Carbodeoxygenation of Biomass: The Carbonylation of Glycerol and Higher Polyols to Monocarboxylic Acids

Abstract: Glycerol is converted to a mixture of butyric and iso-butyric acid via the rhodium or iridium catalysed carbonylation using HI as the co-catalyst. The initial reaction of glycerol with HI results in several intermediates that lead to isopropyl iodide, which upon carbonylation forms butyric and isobutyric acid. At low HI concentration, the intermediate allyl iodide undergoes carbonylation to give vinyl acetic acid and crotonic acid. Higher poly-ols C n H n+2 (OH) n are carbonylated to the corresponding C n+1 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Literature studies revealed that isopropyl iodide (IPI) and allyl iodide are the major intermediates produced in glycerol carbonylation under the reaction conditions used [26,40]. Oxidative addition at rhodium centre results in isomerization to isopropyl and n-propyl metal complexes, [40] and as a result, the carbonylation of IPI results in the formation of both BA and IBA.…”
Section: A Proposed Mechanismmentioning
confidence: 98%
See 1 more Smart Citation
“…Literature studies revealed that isopropyl iodide (IPI) and allyl iodide are the major intermediates produced in glycerol carbonylation under the reaction conditions used [26,40]. Oxidative addition at rhodium centre results in isomerization to isopropyl and n-propyl metal complexes, [40] and as a result, the carbonylation of IPI results in the formation of both BA and IBA.…”
Section: A Proposed Mechanismmentioning
confidence: 98%
“…Reported homogeneous rhodium catalyzed glycerol carbonylation suffer from several disadvantages [25,26]. Homogeneous rhodium catalysts may easily be destroyed during the course of the reaction and they cannot be easily recovered after the reaction for reuse [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of butyric acid and isobutyric acid from glycerol in excellent selectivities has been reported previously by Coskun et al 45 A potential flow diagram for large-scale production, analogous to that of the Cativa process, is shown in Fig. S4 (ESI †).…”
Section: Synthetic Routes To the Four Best Candidates From Biomassmentioning
confidence: 99%
“…This is in part due to the lack of effi-cient routes of reducing the oxygen content of biomass. Developing efficient methods of converting biomass to platform chemicals is essential and severalp otential strategies have been investigated, for example, dehydration, [19] deoxygenation, [21] hydrodeoxygenation, [22,23] carbodeoxygenation [24] and deoxydehydration (DODH). [25][26][27][28] Here, we will focus on deoxydehydration, which is the formal removal of one H 2 Oa nd 1 = 2 O 2 from av icinal diol yielding an alkene functionality (see Scheme 1).…”
Section: Introductionmentioning
confidence: 99%